Implementation of The Binding Agreement for The Sale and Purchase of Land Rights Based on a Notarial Deed in East Jakarta - Dewa Ayu Sinddhisar Smaratungga; R. Ismala Dewi; Enny Koeswarni (LEGAL BRIEF, 2022)
The binding sale and purchase agreement is a preliminary agreement on an agreement to purchase rights to land and or buildings which will later be made and ratified or signed before a notary. Where the parties who are bound by the agreement will fulfill the rights and obligations in accordance with what was conveyed and agreed upon in the binding sale and purchase agreement made. This study aims to find out about the implementation of the binding sale and purchase agreement of land rights based on a notarial deed in East Jakarta. This research is descriptive analytical with an empirical juridical approach, while the data is obtained through library research and field research. Furthermore, the data were analyzed qualitatively. From the results of this study, it will be known that the legal force of the PPJB deed of land rights made by a Notary in the implementation of making his AJB is very strong and is perfect evidence, because the deed is a notarial deed which is an authentic deed and legal protection for the parties. The existence of this PPJB depends on the content or content of the PPJB itself. If one of the parties defaults, it really depends on the strength of the PPJB made, that is, if it is made with a private deed, it is in accordance with the protection of the private deed, while if it is made by or before a Notary then the deed automatically becomes a notarial deed. which has the power of protection in accordance with the protection of the authentic deed.